Effectiveness of a health education program on mothers' knowledge and practice regarding amebiasis - Rawaa K. Abd; Sana Rouis; Khalied Yassen; Mahdi Boutrif (AOSIS, 2023)
This study was conducted to assess the effectiveness of a health education program on mothers' knowledge and practices related to amebiasis. Pre‑ and post‑I and II‑tests were used, along with a two‑group quasi‑experimental design. The study included a convenience sample of 120 mothers, including 60 from the study and 60 from the control group. Out of the entire number of PHCs in Wasit Governorate, seven were used for the study. A three‑part structured questionnaire tests mothers' knowledge of the illness and attitudes about it. The results of this study indicated that there is statistically significant difference between the study and control groups during the post‑test I and post‑test II periods (t=14.968, P=.000 and t=13.731, P=.000, respectively). Data from the study group during the pre‑test period of 31.17(9.14) revealed that (70%) of mothers had bad practices connected to Entameba Histolytica among children. According to the post‑test I results, 47.4 (9.48) respondents, or 70%, identified good practices. The main finding showed that, after the educational program was implemented, mothers' knowledge and practice of amebiasis dramatically increased, with pre‑post implementation differences that are statistically significant.